Structured Design Automation - van Tooren, M. J. L.; van der Elst, S. W. G.; Vermeulen, B. (Cranfield University Press, 2009)
The next stage in product development process evolution should be the automation of labour intensive repetitive steps. The design automation strategy should follow the trend of the supply chain management approach and deliver a flexible framework, allowing local specification and adjustment The proposed Adjoined Design Automation Process Trajectory (ADAPT) and associated tools provide such a framework. It covers the process from fuzzy front-end to the evaluation of automated processes. Considerable lead time and cost savings are shown for electrical component design and the feasibility of a Domain Specific Language approach is an important step towards acceptance of design automation.
Organised by: Cranfield University
Keywords: Design automation; knowledge technologies; knowledge application; value stream mapping